Care of patients undergoing withdrawal of life-sustaining treatments: an ICU nurse perspective - Sung Ok Chang; Dayeong Kim; Yoon Sung Cho; Younjae Oh (BMC Nursing, 2024)
Abstract Background Intensive care unit (ICU) nurses working in South Korea report experiencing uncertainty about how to care for patients undergoing withdrawal of life-sustaining treatments (WLT). A lack of consensus on care guidelines for patients with WLT contributes to uncertainty, ambiguity, and confusion on how to act appropriately within current law and social and ethical norms. To date, little has been discussed or described about how ICU nurses construct meaning about their roles in caring for dying patients in the context of wider social issues about end-of-life care and how this meaning interacts with the ICU system structure and national law. We aimed to better understand how ICU nurses view themselves professionally and how their perceived roles are enabled and/or limited by the current healthcare system in South Korea and by social and ethical norms. Methods This qualitative descriptive study was conducted using in-depth, semi-structured interviews and discourse analysis using Gee’s Tools of Inquiry. Purposive sampling was used to recruit ICU nurses (n = 20) who could provide the most insightful information on caring for patients undergoing WLT in the ICU. The interviews were conducted between December 2021 and February 2022 in three university hospitals in South Korea. Results We identified four categories of discourses: (1) both “left hanging" or feeling abandoned ICU nurses and patients undergoing WLT; (2) socially underdeveloped conversations about death and dying management; (3) attitudes of legal guardians and physicians toward the dying process of patients with WLT; and (4) provision of end-of-life care according to individual nurses’ beliefs in their nursing values. Conclusion ICU nurses reported having feelings of ambiguity and confusion about their professional roles and identities in caring for dying patients undergoing WLT. This uncertainty may limit their positive contributions to a dignified dying process. We suggest that one way to move forward is for ICU administrators and physicians to respond more sensitively to ICU nurses’ discourses. Additionally, social policy and healthcare system leaders should focus on issues that enable and limit the dignified end-of-life processes of patients undergoing WLT. Doing so may improve nurses’ understanding of their professional roles and identities as caretakers for dying patients.